Absorbtion of the photosynthetically active radiation (PAR) in canopy and yield formation by leafy and semi-leafless morphotypes of the pea plant (Pisum sativum L.). - Czerednik, Anna; Nalborczyk, Emil (Plant Breeding and Seed Science, 2000)
An experiment aimed to review differences in the pattern of canopy forming, solar radiation penetration and its use efficiency (RUE) within the canopy of two contrasting pea morphotypes (leafy and semi-leafless) was conducted in the field. The differences in absorption of PAR were significant for both morphotypes in two consecutive years of different climatic conditions. The canopy architecture influenced absorption of PAR, penetration through the canopy and can cresult in different yield forming. For both morphotypes a common linear correlation between intercepted PAR and dry matter accumulation was found until the beginning of pod formation, but then this association was not linear. Differences in CGR and ULRc were significantly bigger in leafy pea morphotypes than in semi-leafless one and the higher values for both were observed at the beginning of pod formation.